Complete mitochondrial genome of Gobiobotia intermedia (Cypriniformes, Cyprinidae). (3rd September 2015) - Li, Bing-Jun; Fu, Feng; Feng, Jun-Rong; Jean, Chuen-Tan; Lee, Cheng-Yu; Han, Chiao-Chuan
Abstract: The complete mitochondrial genome of the Cyprinid fish Gobiobotia intermedia (Cypriniformes, Cyprinidae) was determined. The complete mitogenome sequence has 16, 608 bp and contains the usual 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA (tRNA) genes and a non-coding control region, as those found in other vertebrates, with the gene order identical to that of typical vertebrates. The overall base composition of the heavy strand shows T 26.08%, C 27.25%, A 27.57% and G 19.11%, apparently with a slight AT bias.